Producer–buyer interaction under mass customization: analysis through automotive industry - Arshia Khan; Hans-Dietrich Haasis (Logistics Research, 2016)
Automotive companies have successfully adopted mass customization. However, this production method has complicated the sales process as the customer has to go through a lot of steps to specify the product. Thus, it is important that the sales process is modified to make the producer-buyer interaction efficient in mass customization. There is no study that examines whether the modifications in the sales processes of the automotive industry are according to the needs of mass customization. In this context, we investigate this relation for two leading automotive companies, for the customers of the USA, from 2008 till 2015. By applying statistical calculations, we observe that the increase in mass customization has actually declined customer satisfaction of the sales process. Hence, there is a further need to modify the sales process according to the needs of mass customization. Otherwise, the long-term success of mass customization of a car manufacturer is at risk.
Keywords: 650; Producer-buyer linkage; Sales process; Mass customization; Automotive industry